An Hourglass-Shaped Wireless and Passive Magnetoelastic Sensor with an Improved Frequency Sensitivity for Remote Strain Measurements - Ren, Limin (Sensors (Basel), 2020)
The conventional magnetoelastic resonant sensor suffers from a low detecting sensitivity problem. In this study, an hourglass-shaped magnetoelastic resonant sensor was proposed, analyzed, fabricated, and tested. The hourglass-shaped magnetoelastic resonant sensor was composed of an hourglass and a narrow ribbon in the middle. The hourglass and the narrow ribbon increased the detection sensitivity by reducing the connecting stress. The resonant frequency of the sensor was investigated by the finite element method. The proposed sensor was fabricated and experiments were carried out. The tested resonance frequency agreed well with the simulated one. The maximum trust sensitivity of the proposed sensor was 37,100 Hz/strain. The power supply and signal transmission of the proposed sensor were fulfilled via magnetic field in a wireless and passive way due to the magnetostrictive effect. Parametric studies were carried out to investigate the influence of the hourglass shape on the resonant frequency and the output voltage. The hourglass-shaped magnetoelastic resonant sensor shows advantages of high sensitivity, a simple structure, easy fabrication, passiveness, remoteness, and low cost.